Management Of The Revitalization Of Vocational School (SMK) Revitalization As An Effort To Improve The Quality And Competitiveness Of Graduates (Study At SMKN 3 Pamekasan) - Winda Fashihah; Suryadi; Ainul Hayat (Journal of Innovative and Creativity, 2025)
The Vocational High School Revitalization Policy (SMK) is a Presidential Instruction (Inpres) Number 9 of 2016 concerning "Vocational High School Revitalization in the Context of Improving the Quality and Competitiveness of Indonesian Human Resources". The government has made many efforts to achieve the quality of education, but in this case strategic management is needed in changing the order of development in Indonesia. This study uses a descriptive type of research with a qualitative approach located in Pamekasan Regency, while the site is at SMKN 3 Pamekasan. The data sources used are primary and secondary data sources. Data collection techniques through observation, interviews and documentation. While the research instrument is the researcher himself, and several other supporting tools. The results showed that the management of the vocational revitalization strategy in improving the quality and competitiveness of graduates at SMKN 3 Pamekasan included 3 processes, namely: 1). Strategic planning starting from the formulation of the vision, mission and goals has involved all elements of the school starting from the principal, vice chairman of the curriculum, vice chairman of student affairs, vice chairman of public relations, vice chairman of quality management, head of departmental programs and school committees by analyzing the school environment using a SWOT analysis based on quality report. 2). The implementation of the strategy includes the determination of school policies and then the motivation and direction from the principal in the form of rewards for educators who carry out their duties well. Likewise, the allocation of human resources consisting of productive, normative and adaptive teachers is in accordance with their respective competencies in their fields. This strategic implementation certainly needs to be supported by school culture, at SMKN 3 Pamekasan already has a culture that supports the achievement of school goals, namely professionalism, discipline and responsibility. 3) Evaluation of strategies in improving the quality and competitiveness of graduates at SMKN 3 Pamekasan includes several activities, namely monitoring all the results of activities from planning and implementing strategies, measuring individual performance, and taking corrective steps.